2012
DOI: 10.1111/j.1755-3768.2011.02351.x
|View full text |Cite
|
Sign up to set email alerts
|

Time to consider a new treatment protocol for aggressive posterior retinopathy of prematurity?

Abstract: ABSTRACT.Purpose: To discuss treatment modalities for aggressive posterior retinopathy of prematurity (AP-ROP). Methods: The medical charts of all infants with AP-ROP at Uppsala University Hospital, Sweden, during a 2-year period (2009 and 2010) were reviewed. Eight infants (16 eyes) with a mean gestational age of 23.8 weeks and a mean birth weight of 592 g were treated with laser and ⁄ or intravitreal injections of bevacizumab (0.4 and 0.625 mg). RetCam photography was used to document the retinal appearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 34 publications
(45 reference statements)
1
38
0
1
Order By: Relevance
“…Vannak közlések arra nézve, hogy négyes stá-diumban, ahol sajnos a parciális retinaleválás része az agresszív ROP-nak, szemlencsét megtartó vitrectomia látásmentő beavatkozás lehet. Az anti-VEGF-kezelés hatékonyságának alátámasztása további kutatást igényel [17]. Egyéb potenciális terápiás lehetőségek közül a ROP 1. fázisában alkalmazott IGF-1-IGFBP3 komplex (inzulinszerű növekedési faktor -inzulinszerű növeke-dési faktor kötő fehérje komplex 3) szubsztitúció már svéd kutatók által indított klinikai II.…”
Section: A Rop Kezeléseunclassified
“…Vannak közlések arra nézve, hogy négyes stá-diumban, ahol sajnos a parciális retinaleválás része az agresszív ROP-nak, szemlencsét megtartó vitrectomia látásmentő beavatkozás lehet. Az anti-VEGF-kezelés hatékonyságának alátámasztása további kutatást igényel [17]. Egyéb potenciális terápiás lehetőségek közül a ROP 1. fázisában alkalmazott IGF-1-IGFBP3 komplex (inzulinszerű növekedési faktor -inzulinszerű növeke-dési faktor kötő fehérje komplex 3) szubsztitúció már svéd kutatók által indított klinikai II.…”
Section: A Rop Kezeléseunclassified
“…Spandau et al [19] found that after IVI of bevacizumab, vascularization of the retina was completed in the 65th week. Menke et al [20] reported that after IVI of ranibizumab, vascularization of the retina was completed between the 3rd and 6th months without recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…27 Ever since the introduction of bevacizumab as a therapeutic choice, its possible toxicity to the retina has been an issue of great concern and object of intense research. 28,29 Clinical and histological studies testing the effect of bevacizumab on rabbit retinal tissue have failed to show tissue toxicity. 21,30 Nevertheless, most safety studies published to date have evaluated the effect of bevacizumab in adult animals, rather than assessing its safety profile in the developing retina.…”
Section: Discussionmentioning
confidence: 99%